Institutional engineering and political fragmentation: a critical evaluation of the parliamentary threshold policy in Indonesia - Muhammad Asmawi; Dani Muhtada; Martitah Martitah (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
This article examines the democratic consequences of Indonesia’s parliamentary threshold as an instrument of electoral institutional engineering. Its urgency lies in the growing tension between efforts to simplify parliamentary fragmentation and the constitutional imperative to protect meaningful political representation in a plural society. Using a descriptive qualitative design and a structured literature review informed by PRISMA reporting principles, the study analyzes regulatory developments, official election results, academic literature, and comparative experiences from Germany, Turkey, and Thailand. The article’s novelty lies in evaluating the parliamentary threshold not only as a mechanism for party-system simplification, but also as a democratic filter that affects proportionality, inclusion, and legitimacy. The findings show that the threshold has reduced the number of parties entering the Indonesian House of Representatives, yet has not resolved weak party institutionalization, coalition fluidity, or elite-centered politics. The 2024 election illustrates this dilemma, as 17,304,303 votes, or approximately 11.40 percent of valid national legislative votes, were not converted into seats. Drawing on Dahl, Lijphart, Duverger, Pitkin, and Mainwaring and Scully, this article contributes a normative-institutional framework for reassessing Indonesia’s threshold policy and recommends evidence-based recalibration following the Constitutional Court’s conditional ruling.